Improvement of humification and mechanism of nitrogen transformation during pig manure composting with Black Tourmaline. (July 2020) - Ren, Xiuna; Wang, Quan; Zhang, Yue; Awasthi, Mukesh Kumar; He, Yifeng; Li, Ronghua; Zhang, Zengqiang
Graphical abstract: Highlights: Black Tourmaline (TM) were added into pig manure and sawdust for composting. Maximum value of HA/FA was observed in 10% TM added treatment. TM promoted the transformation from NH4 + -N to amino organic nitrogen. 10% TM added treatment had the minimal nitrogen loss caused by NH3 and N2 O. Total organic carbon was main factor driving changes of enzymatic activities. Abstract: This study aimed to reveal the role of Black Tourmaline (TM) in the humification enhancement and the mechanism of nitrogen transformation during pig manure composting. Results showed that adding TM promoted the maturity and improved the humification degree by 20.13–33.77%. And TM was beneficial for the transformation from NH4 + -N to amino organic nitrogen to fix more nitrogen in compost mass. Then NH3 and N2 O volatilization were decreased by 22.88–34.76% and 69.79–87.47% by comparison with the control, and the minimum value in nitrogen loss (26.78%) was observed in the 10% TM blended treatment. Furthermore, through RDA analysis, the protease an upmost contributor to nitrogen transformation. Meanwhile, total organic carbon was dominant factor affected enzymatic activities. Therefore, 10% TM was suggested to reduce nitrogen loss and increase humification in this research. Deeply related research in gene and specific addition amounts of TM will be investigated later.